Analisis Faktor yang Mempengaruhi Gamers PC dan Konsol Beralih ke Game Mobile menggunakan Metode K-Means Clustering - Reynaldo, Yohanes; Triayudi, Agung; Ningsih, Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
This research was conducted because of the trend that has occurred in the last 5 years in Indonesia, namely the emergence of mobile-based games that are played by many people in Indonesia from small children to adults. With the emergence of mobile-based games in Indonesia, the appeal of PC and console-based games has become less attractive. This study aims to analyze the factors that influence PC and console-based gamers to switch to mobile-based games. The method used in this study is K-means Clustering and the supporting data from this study include the age factor of the game players and the duration of playing the game as a parameter. The technique of collecting data is through a google form questionnaire. The subject of the research is the Indonesian gamers forum contained in facebook forums.